Benziodoxole-Based Hypervalent Iodine Reagents in Organic Synthesis - Zhdankin, Viktor V. (Current Organic Synthesis, 2005)
Five-membered hypervalent iodine heterocycles derived from benziodoxole and benziodazole oxide have recently emerged as reagents of choice for various synthetically useful oxidative transformations. In particular, IBX (2-iodoxybenzoic acid) and DMP (Dess-Martin periodinane) are widely used for the selective oxidation of primary and secondary alcohols and for a variety of other important oxidations. IBX-amides and IBX-esters are a new class of pentavalent iodine reagents with a pseudo-benziodoxole structure and a reactivity pattern similar to IBX.
Keywords: hypervalent iodine